2010
DOI: 10.1007/s12665-009-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

Large differential land subsidence and earth fissures in Jiangyin, China

Abstract: Jiangyin County is in the infamous SuXi-Chang land subsidence area caused by excessive groundwater withdrawal in Jiangsu province, China. The maximum accumulated land subsidence reached 1,310 mm near the centre of the subsiding trough in 2006 in southern Jiangyin, and earth fissures of significant vertical offsets have been observed at Changjing, Hetang and Wenlin which form an arc towards the subsidence trough. An ancient Yangtze River course is found underlying and passing through the depression in southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…distributes along the NE direction and locates in the northern research area, which is the core area of surface subsidence with subsidence depth of more than 3 m and basically distributes along the uplift of the buried bedrocks ( Figure 1) (Liu 2011). Taking Changjing of Wuxi as an example, their shallow seismic lines indicate a good relation between the earth fissures and the uplift of bedrocks, which have buried depth between 105 and 152 m, in the NE direction (Wang et al 2010). Above the bedrocks, there are various alluvial layers of hard plastic silty clays, clays and sands.…”
Section: Distributionmentioning
confidence: 99%
“…distributes along the NE direction and locates in the northern research area, which is the core area of surface subsidence with subsidence depth of more than 3 m and basically distributes along the uplift of the buried bedrocks ( Figure 1) (Liu 2011). Taking Changjing of Wuxi as an example, their shallow seismic lines indicate a good relation between the earth fissures and the uplift of bedrocks, which have buried depth between 105 and 152 m, in the NE direction (Wang et al 2010). Above the bedrocks, there are various alluvial layers of hard plastic silty clays, clays and sands.…”
Section: Distributionmentioning
confidence: 99%
“…It is a typical geological formation in which the second confined aquifer buried is widely distributed and has a high water yield, which led to the large-scale development and utilization of groundwater resources in 1970. The long-term overexploitation of groundwater and the sharp decline in the water level resulted in severe land subsidence in the Su-Xi-Chang area, and an earth fissure was subsequently formed [6].…”
Section: Structurementioning
confidence: 99%
“…The direction of the two main cracks is the same, and the main fracture zone is distributed in the NE direction where the earth fissure situation is the most serious. F8 once crossed a nine-story building of the local Shuangping group and destroyed it [6]. Subsequent investigation found that the old site had been completely demolished, but the earth fissure was still active.…”
Section: Earth Fissures In Chaqiao (F6 1992)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such occurrences have been documented worldwide, that the reports concentrate in southeastern US (Arizona, California, Idaho, Nevada, Texas and Utah) [1,4,5]; China, in the provinces on the lower Yellow River basin (Shaanxi, Shanxi, northern Henan, Hebei, Shandong, Jiangu and Anhui) [6][7][8], and in Shanghai [9]; Thailand in Bangkok [10]; Italy in Venice [11]; and central México in the cities of Aguascalientes, Celaya [12,13], Irapuato, Mexico City [14], Morelia [2,3,15]; Querétaro [16] and Salamanca [17,18].…”
Section: Introductionmentioning
confidence: 99%